A Descriptive Study to Assess the Knowledge and Attitude Regarding Higher Education among Nursing Students in Selected Nursing Colleges of Noida (International Journal of Nursing Education, 2021)
Introduction: Education is an endless journey through knowledge and enlightenment. Higher Educationamong nurses has gained lot of interest over the past few decades. Obtaining higher education has longbeen an expectation for the ongoing professional development of the registered nurse. Aim of thestudy was to assess the knowledge and attitude regarding higher education among Nursing studentsin selected Nursing colleges of Noida. Objectives of the study were to assess knowledge of nursingstudents regarding higher education in nursing and to determine attitude of nursing students regardinghigher education in nursing.Method: A descriptive research design was used for the study. Sample size consist of 100 nursingstudents (B.Sc. nursing final year and GNM internship) by random sampling method. Data was collectedby administering structured knowledge questionnaire and attitude scale. Data analysis was chalked outby employing descriptive and inferential statistics.Result: Result regarding Knowledge revealed that 27% of students have good knowledge, 68% havemoderate and 5% have poor knowledge regarding higher education and Attitude score represents that50.59% had favourable attitude and 41% had unfavourable attitude towards higher education.Conclusion: According to this study the maximum number of samples (68%) have moderate knowledgeregarding higher education and maximum number of samples (59%) have favourable attitude towardshigher education.